Molecular sieve catalyst as well as preparation method and application thereof

By loading bimetallic Cu and Fe on the UZM-35 molecular sieve support, the synergistic effect is used to solve the shortcomings of existing catalysts in high and low temperature activity and N2O generation amount, and the efficient nitrogen oxide removal of the catalyst is achieved.

CN119857522APending Publication Date: 2025-04-22GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510055934.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing nitrogen oxide catalysts have shortcomings in high and low temperature activity and N2O generation amount, and cannot meet increasingly stringent emission standards.

Method used

UZM-35 molecular sieve is used as a support to support bimetallic Cu and Fe. Through the synergistic effect between Cu and Fe and UZM-35 support, the high and low temperature activity and hydrothermal stability of the catalyst are improved, and the amount of N2O is reduced.

Benefits of technology

The excellent activity of the catalyst at high and low temperatures is achieved, the activity temperature window is broadened, the N2O generation amount is reduced, and the problem of high emission of N2O pollutants in Cu-based molecular sieve is solved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119857522A_ABST
    Figure CN119857522A_ABST
Patent Text Reader

Abstract

The invention provides a molecular sieve catalyst and a preparation method and application thereof.The molecular sieve catalyst comprises UZM-35 and Cu and Fe loaded on the UZM-35, and the preparation method comprises the steps that an NH4-UZM-35 molecular sieve and a copper source are subjected to an ion exchange reaction, Cu-UZM-35 is obtained after first roasting, then Fe loading is conducted on the Cu-UZM-35 in an iron source solution, and the Cu-UZM-35 is obtained after second roasting. And after second roasting and third roasting, Cu / Fe-UZM-35 is obtained. By utilizing the synergistic effect between the metals Cu and Fe and the UZM-35 carrier, the catalyst can give consideration to high and low temperature activity and has good hydrothermal stability, the generation amount of a by-product N2O is relatively low, the active window of the molecular sieve is effectively widened, and the problem of emission control of N2O pollutants of the Cu-based molecular sieve is solved; moreover, the preparation process is simple, convenient to operate, green and efficient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nitrogen oxide reduction, and relates to a molecular sieve catalyst and a preparation method and application thereof. Background Art

[0002] Nitrogen oxides (NO x ) is a common pollutant in the atmosphere, NO x It will cause many harms to the environment and is an important precursor pollutant that causes environmental problems such as acid rain, haze, and photochemical smog. x The emission of NO in diesel vehicle exhaust accounts for 88.4% of the total automobile emission. x The removal of NO has become a hot topic for researchers. x In the method, NH3 is used as a reducing agent to reduce NO x Selective catalytic reduction of NO x (NH3-SCR) method, because its reaction temperature is low, NO x It has the advantages of high conversion rate and no secondary pollution of the generated N2, and is widely used in fields such as fixed source flue gas denitrification and diesel vehicle exhaust purification.

[0003] Due to the large temperature variation of diesel vehicle exhaust gas and the low exhaust temperature during the cold start phase, NH3-SCR catalysts require a wide operating temperature window and excellent low-temperature activity. In addition, the regeneration of the diesel vehicle particulate filter (DPF) will place the NH3-SCR catalyst in a high temperature and high humidity environment, so the NH3-SCR catalyst requires good hydrothermal stability. SCR catalysts are divided into oxides and molecular sieves. The classic SCR catalyst is a V-containing catalyst, which has the advantage of good resistance to SO2 poisoning, but has a narrow operating window, low high-temperature N2 selectivity, and metal V is biologically toxic.

[0004] Other non-V catalysts, such as oxide catalysts Ce-W, Fe-Ti, and Cu-based or Fe-based molecular sieve catalysts with molecular sieve as carrier, have become hot research topics due to their wide temperature window and good low-temperature activity. However, Cu-based molecular sieves have excellent low-temperature activity, but insufficient medium- and high-temperature activity, and a large amount of N2O is generated, which cannot meet the increasingly stringent N2O emission standards; Fe-based molecular sieves often have excellent high-temperature activity, a small amount of N2O generation, but insufficient low-temperature activity.

[0005] Therefore, how to develop a nitrogen oxide catalyst that has both high and low temperature catalytic activity and low N2O production is an urgent problem to be solved. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a molecular sieve catalyst and its preparation method and application. The molecular sieve catalyst provided by the present invention uses UZM-35 molecular sieve as a carrier and loads bimetallic Cu and Fe. Thanks to the synergistic effect between Cu and Fe and the UZM-35 carrier, the catalyst can take into account both high and low temperature activity, thereby effectively broadening the active temperature window of the molecular sieve; and the molecular sieve catalyst provided by the present invention has good hydrothermal stability, and the generation of byproduct N2O is lower, thereby solving the problem of high N2O pollutant emissions of Cu-based molecular sieves; in addition, the preparation method provided by the present invention is simple and suitable for large-scale use.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a molecular sieve catalyst, comprising UZM-35 and Cu and Fe supported on the UZM-35.

[0009] In the present invention, through the coupling of bimetallic Cu and Fe, and the synergistic effect thereof with UZM-35, the catalyst has the advantages of both Cu-based catalysts and Fe-based catalysts, retaining both the low-temperature activity of the Cu-based catalyst and the high-temperature activity and the low N2O generation characteristics of the Fe-based catalyst, thereby effectively broadening the active temperature window of the molecular sieve.

[0010] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.

[0011] Preferably, the Cu loading is 0.5-5wt%, for example 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0012] Preferably, the loading amount of Fe is 0.5-5wt%, for example, 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt% or 5wt%, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0013] In the present invention, the high and low temperature activity of the catalyst can be regulated by adjusting the loading amount of Cu and Fe according to actual needs; the loading amount of Cu and Fe is controlled at 0.5-5wt%, which can better take into account the high and low temperature activity of the catalyst and reduce the generation amount of N2O.

[0014] In a second aspect, the present invention provides a method for preparing a molecular sieve catalyst as described in the first aspect, the preparation method comprising: subjecting an NH4-UZM-35 molecular sieve to an ion exchange reaction with a copper source, obtaining Cu-UZM-35 after a first calcination, and then loading the Cu-UZM-35 with Fe in an iron source solution, and obtaining Cu / Fe-UZM-35 after a second calcination and a third calcination.

[0015] In the present invention, Cu / Fe-UZM-35 is prepared by three calcinations. This calcination method can enable Cu and Fe to select more stable sites for loading on the UZM-35 carrier, so that the prepared catalyst has better catalytic activity and stability.

[0016] Preferably, the copper source includes any one of copper nitrate, copper acetate or copper carbonate, or a combination of at least two of them.

[0017] The ion exchange reaction comprises: dispersing the NH4-UZM-35 molecular sieve in a solvent, adding a copper source, and performing ion exchange.

[0018] Preferably, the solid-liquid ratio of the NH4-UZM-35 to the solvent is 1:(20-150), for example 1:20, 1:30, 1:40, 1:50, 1:60, 1:70, 1:80, 1:90, 1:100, 1:110, 1:120, 1:130, 1:140 or 1:150, etc., but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0019] Preferably, the temperature of the ion exchange reaction is 40-100°C, for example 40°C, 50°C, 60°C, 70°C, 80°C, 90°C or 100°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0020] Preferably, the ion exchange reaction time is 5 to 24 hours, such as 5 hours, 10 hours, 15 hours, 20 hours or 24 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0021] Preferably, the ion exchange reaction is carried out under stirring, and the stirring speed is 100 to 1000 r / min, for example, 100 r / min, 200 r / min, 300 r / min, 400 r / min, 500 r / min, 600 r / min, 700 r / min, 800 r / min, 900 r / min or 1000 r / min, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0022] Preferably, the product after the ion exchange reaction is subjected to a first cooling process, a first solid-liquid separation process, a first washing process and a first drying process in sequence.

[0023] Preferably, the first drying temperature is 80-180°C, for example 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0024] Preferably, the first drying time is 8 to 24 hours, for example 8 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0025] Preferably, the heating rate of the first calcination is 0.5 to 10°C / min, for example, 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0026] Preferably, the first calcination temperature is 500-800°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0027] Preferably, the holding time of the first calcination is 5 to 10 hours, such as 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0028] Preferably, the method of loading Fe includes any one of an incipient wetness impregnation method, an impregnation method or an ion exchange method, preferably an incipient wetness impregnation method.

[0029] Preferably, the iron source includes any one of ferrous chloride, ferrous acetate, ferrous sulfate or ferrous oxalate, or a combination of at least two thereof.

[0030] In the present invention, by selecting ferrous salt as the iron source, compared with trivalent ferrous salt, ferrous ions are more likely to reach charge balance with divalent anions in the molecular sieve structure during the impregnation process, and divalent ferrous ions have a smaller atomic radius and smaller steric hindrance, so it is more conducive to the impregnation of Fe into Cu-UZM-35, thereby better realizing the loading of Fe.

[0031] Preferably, the incipient wetness impregnation method comprises: adding the iron source solution dropwise into the Cu-UZM-35 under grinding conditions, and letting the solution stand.

[0032] Preferably, the mass ratio of the Cu-UZM-35 to the solvent in the iron source solution is 1:(1-5), such as 1:1, 1:2, 1:3, 1:4 or 1:5, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0033] In the present invention, the impregnation effect of Fe can be further improved by adjusting the mass ratio of Cu-UZM-35 to the solvent in the iron source solution.

[0034] Preferably, the grinding temperature is 20-60°C, such as 20°C, 30°C, 40°C, 50°C or 60°C, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0035] Preferably, the grinding time is 0.5 to 3 h, such as 0.5 h, 1 h, 1.5 h, 2 h, 2.5 h or 3 h, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0036] Preferably, the standing time is 1 to 24 hours, for example, 1 hour, 3 hours, 5 hours, 7 hours, 9 hours, 11 hours, 13 hours, 15 hours, 17 hours, 19 hours, 21 hours or 24 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0037] Preferably, the second calcination is carried out in a protective gas atmosphere, preferably nitrogen.

[0038] Preferably, the heating rate of the second calcination is 0.5 to 10°C / min, for example, 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0039] Preferably, the temperature of the second calcination is 500-800°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0040] Preferably, the holding time of the second calcination is 5 to 10 hours, such as 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0041] Preferably, the product after the second calcination is subjected to a second solid-liquid separation, a second washing and a second drying treatment in sequence.

[0042] Preferably, the second drying temperature is 80-180°C, for example 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C or 180°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0043] Preferably, the second drying time is 8 to 24 hours, for example 8 hours, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours or 24 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0044] Preferably, the third calcination is performed in an air atmosphere.

[0045] In the present invention, the second calcination is carried out in a protective gas atmosphere, which can retain more ferrous ions and is conducive to loading more Fe on the molecular sieve; the third calcination is carried out in an air atmosphere, which is conducive to converting most of the ferrous ions loaded on the carrier into trivalent ferrous ions, completely stabilizing the iron ions loaded on the catalyst, and avoiding the oxidation of divalent iron in the subsequent air.

[0046] Preferably, the heating rate of the third calcination is 0.5-10°C / min, for example, 0.5°C / min, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min or 10°C / min, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0047] Preferably, the temperature of the third calcination is 500-800°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C or 800°C, but is not limited to the listed values, and other unlisted values ​​within the range are also applicable.

[0048] Preferably, the holding time of the third calcination is 5 to 10 hours, for example, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours or 10 hours, but is not limited to the listed values, and other values ​​not listed within the range are also applicable.

[0049] In the present invention, different temperatures and / or times in the first, second and third calcination processes can be selected according to the requirements for catalyst quality. By controlling the temperature at 500-800° C. and the time at 5-10 h, the stability of Cu and / or Fe loaded in the carrier can be further improved, which is more conducive to improving the catalyst activity and stability.

[0050] As a preferred technical solution of the present invention, the preparation method comprises the following steps:

[0051] (1) NH4-UZM-35 and a solvent are mixed at a solid-liquid ratio of 1:(20-150), a copper source is added thereto, and then an ion exchange reaction is carried out at 40-100° C. for 5-24 hours at a stirring speed of 100-1000 r / min, and after cooling, solid-liquid separation and washing, a first drying treatment is carried out at 80-180° C. for 8-24 hours, and the temperature is increased to 500-800° C. at a heating rate of 0.5-10° C. / min, and the temperature is kept for 5-10 hours to obtain Cu-UZM-35;

[0052] (2) according to the mass ratio of Cu-UZM-35 to solvent being 1:(1-5), a solvent is added to an iron source to prepare an iron source solution, and then the iron source solution is added dropwise to the Cu-UZM-35 under grinding conditions of 20-60°C. After the process lasts for 0.5-3h, the mixture is allowed to stand for 1-24h. Subsequently, the mixture is heated to 500-800°C at a heating rate of 0.5-10°C / min in a nitrogen atmosphere, and kept warm for 5-10h. The product after the first calcination is filtered and washed in turn, and then dried at 80-180°C for 8h-24h. Then, the mixture is heated to 500-800°C at a heating rate of 0.5-10°C / min in an air atmosphere, and kept warm for 5-10h to obtain Cu / Fe-UZM-35.

[0053] The copper source includes any one of copper nitrate, copper acetate or copper carbonate, or a combination of at least two thereof;

[0054] The iron source includes any one of ferrous chloride, ferrous acetate, ferrous sulfate or ferrous oxalate, or a combination of at least two thereof.

[0055] In a third aspect, the present invention further provides a use of the molecular sieve catalyst as described in the first aspect in the conversion of nitrogen oxides.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] The present invention uses UZM-35 molecular sieve as a carrier, loads a certain content of metal Cu and Fe, fully utilizes the synergistic effect between the metal Cu and Fe and the UZM-35 carrier, improves the catalytic low-temperature activity and reduces the amount of N2O generated, broadens the activity window of the molecular sieve, and solves the emission control problem of N2O pollutants in the Cu-based molecular sieve; and the preparation process is simple, the operation is convenient, and it is green and efficient. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 The molecular sieve catalysts provided in Example 1 and Comparative Examples 1 and 2 before aging and at different temperatures are NO x Conversion rate graph.

[0059] Figure 2 The molecular sieve catalysts provided in Example 1 and Comparative Examples 1 and 2 are NO2-containing catalysts after aging at different temperatures. x Conversion rate graph.

[0060] Figure 3 It is a curve diagram of N2O generation at different temperatures of the molecular sieve catalyst provided in Example 1 and Comparative Examples 1 and 2 before aging. DETAILED DESCRIPTION

[0061] The technical scheme of the present invention is further illustrated by specific examples below. Those skilled in the art should understand that the examples are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.

[0063] Example 1

[0064] This embodiment provides a Cu / Fe-UZM-35 molecular sieve catalyst, including a UZM-35 molecular sieve carrier and active components Cu and Fe loaded on the UZM-35 molecular sieve carrier, wherein the loading amount of Cu is 2.6wt% and the loading amount of Fe is 0.8wt%.

[0065] The preparation method comprises the following steps:

[0066] (1) Weigh 2 g of NH4-UZM-35, mix it with water at a solid-liquid ratio of 1:50, add 7.986 g of copper acetate, mix well, place at 60°C and stir for 8 h at a speed of 300 r / min, cool to 30°C after stirring, filter, and dry at 100°C for 12 h. After drying, calcine at 600°C, 6 h, 5°C / min.

[0067] (2) Weigh 1g of the 2.6wt% Cu-UZM-35 obtained in step (1) and place it in a mortar. According to the mass ratio of Cu-UZM-35 to water of 1:1.5, 0.018g of ferrous chloride is used to prepare a ferrous chloride solution. The impregnation process is carried out at 40°C, first drip 5d of ferrous chloride liquid, grind for a while, then drip and grind again until the solution is added, the grinding time is 0.5h, seal and stand for 10h; then carry out the first roasting under N2 atmosphere, the roasting conditions are: 650°C, 7h, 5°C / min, wash with deionized water after roasting, filter and dry, and dry at 100°C for 12h; then carry out the second roasting under air atmosphere, the roasting conditions are: 600°C, 7h, 5°C / min, and finally obtain 2.6wt%Cu / 0.8wt%Fe-UZM-35.

[0068] Example 2

[0069] This embodiment provides a Cu / Fe-UZM-35 molecular sieve catalyst, including a UZM-35 molecular sieve carrier and active components Cu and Fe loaded on the UZM-35 molecular sieve carrier, wherein the loading amount of Cu is 0.5wt% and the loading amount of Fe is 5wt%.

[0070] The preparation method comprises the following steps:

[0071] (1) Weigh 2 g of NH4-UZM-35, mix it with water at a solid-liquid ratio of 1:20, add 0.08 g of copper acetate, mix well, place at 40°C and stir for 5 h at a speed of 100 r / min, cool to 10°C after stirring, filter, and dry at 80°C for 8 h. After drying, calcine at 500°C, 5 h, 0.5°C / min.

[0072] (2) Weigh 1g of 0.5wt% Cu-UZM-35 obtained in step (1) and place it in a mortar. According to the mass ratio of Cu-UZM-35 to water of 1:5, 0.128g of ferrous oxalate is used to prepare a ferrous oxalate solution. The impregnation process is carried out at 20°C, first drip 5d of ferrous oxalate liquid, grind for a while, then drip and grind again until the solution is added, the grinding time is 3h, seal and stand for 24h; then carry out the first roasting under N2 atmosphere, the roasting conditions are: 500°C, 5h, 0.5°C / min, wash with deionized water after roasting, filter and dry, and dry at 80°C for 8h; then carry out the second roasting under air atmosphere, the roasting conditions are: 500°C, 5h, 0.5°C / min, and finally obtain 0.5wt% Cu / 5wt% Fe-UZM-35.

[0073] Example 3

[0074] This embodiment provides a Cu / Fe-UZM-35 molecular sieve catalyst, including a UZM-35 molecular sieve carrier and active components Cu and Fe loaded on the UZM-35 molecular sieve carrier, wherein the loading amount of Cu is 5wt% and the loading amount of Fe is 0.5wt%.

[0075] The preparation method comprises the following steps:

[0076] (1) Weigh 2 g of NH4-UZM-35, mix it with water at a solid-liquid ratio of 1:150, add 23.96 g of copper acetate, mix well, place at 100°C and stir for 24 h at a speed of 1000 r / min, cool to 50°C after stirring, filter, and dry at 180°C for 24 h. After drying, calcine at 800°C, 10 h, and 10°C / min.

[0077] (2) Weigh 1g of the 5wt% Cu-UZM-35 obtained in step (1) and place it in a mortar. According to the mass ratio of Cu-UZM-35 to water of 1:1, 0.0135g of ferrous sulfate is used to prepare a ferrous sulfate solution. The impregnation process is carried out at 60°C, first drip 5d of ferrous sulfate liquid, grind for a while, then drip and grind again until the solution is added, the grinding time is 2h, seal and stand for 1h; then carry out the first roasting under N2 atmosphere, the roasting conditions are: 800°C, 10h, 10°C / min, wash with deionized water after roasting, filter and dry, and dry at 180°C for 24h; then carry out the second roasting under air atmosphere, the roasting conditions are: 800°C, 10h, 10°C / min, and finally obtain 5wt% Cu / 0.5wt% Fe-UZM-35.

[0078] Example 4

[0079] The difference between this embodiment and embodiment 1 is that the iron salt is ferrous acetate.

[0080] The remaining preparation parameters are the same as those in Example 1.

[0081] Example 5

[0082] The difference between this embodiment and embodiment 1 is that the copper salt is copper acetate.

[0083] The remaining preparation parameters are the same as those in Example 1.

[0084] Example 6

[0085] The difference between this embodiment and embodiment 1 is that in step (2), the Fe loading method is an impregnation method, and the specific process is as follows:

[0086] Weigh 1 g of the 2.6 wt% Cu-UZM-35 obtained in step (1) and place it in a beaker. Add 50 mL of water according to the solid-liquid ratio of Cu-UZM-35 to water of 1:50, then add 0.018 g of ferrous chloride, stir at room temperature for 30 min, then transfer to a rotary evaporator and spin dry, and scrape out the powder.

[0087] The remaining preparation parameters are the same as those in Example 1.

[0088] Example 7

[0089] The difference between this embodiment and embodiment 1 is that in step (2), the Fe loading method is an ion exchange method, and the specific process is as follows:

[0090] Weigh 1 g of 2.6 wt% Cu-UZM-35, mix it with water at a solid-liquid ratio of 1:50, add 0.063 g of ferrous chloride, mix well and place at 60 ° C and stir for 8 h at a speed of 300 r / min. After stirring, cool to 30 ° C, filter, and dry at 100 ° C for 12 h.

[0091] The remaining preparation parameters are the same as those in Example 1.

[0092] Example 8

[0093] The difference between this embodiment and embodiment 1 is that the loading amount of Fe is 0.2 wt % and the mass of ferrous chloride added in step (2) is 0.005 g.

[0094] The remaining preparation parameters are the same as those in Example 1.

[0095] Example 9

[0096] The difference between this embodiment and embodiment 1 is that the loading amount of Fe is 6 wt % and the mass of ferrous chloride added in step (2) is 0.136 g.

[0097] The remaining preparation parameters are the same as those in Example 1.

[0098] Example 10

[0099] The difference between this embodiment and embodiment 1 is that the loading amount of Cu is 0.3 wt % and the amount of copper acetate added in step (1) is 0.04 g.

[0100] The remaining preparation parameters are the same as those in Example 1.

[0101] Embodiment 11

[0102] The difference between this embodiment and embodiment 1 is that the loading amount of Cu is 6 wt % and the amount of copper acetate added in step (1) is 28.05 g.

[0103] The remaining preparation parameters are the same as those in Example 1.

[0104] Example 12

[0105] The difference between this embodiment and embodiment 1 is that the first, second and third calcination temperatures in steps (1) and (2) are all 400°C.

[0106] The remaining preparation parameters are the same as those in Example 1.

[0107] Embodiment 13

[0108] The difference between this embodiment and embodiment 1 is that the first, second and third calcination temperatures in steps (1) and (2) are all 1000°C.

[0109] The remaining preparation parameters are the same as those in Example 1.

[0110] Embodiment 14

[0111] The difference between this embodiment and embodiment 1 is that the first, second and third roasting times in steps (1) and (2) are all 3 hours.

[0112] The remaining preparation parameters are the same as those in Example 1.

[0113] Embodiment 15

[0114] The difference between this embodiment and embodiment 1 is that the first, second and third roasting times in steps (1) and (2) are all 12 hours.

[0115] The remaining preparation parameters are the same as those in Example 1.

[0116] Comparative Example 1

[0117] The difference between this comparative example and Example 1 is that in this comparative example, the molecular sieve catalyst is 0.8 wt% Fe-UZM-35, step (1) is not performed during the preparation process, and step (2) is performed directly, and the Cu-UZM-35 in step (2) is replaced by NH4-UZM-35.

[0118] The remaining preparation parameters are the same as those in Example 1.

[0119] Comparative Example 2

[0120] The difference between this comparative example and Example 1 is that in this comparative example, the molecular sieve catalyst is 2.6 wt% Cu-UZM-35, and only step (1) is performed during the preparation process, and step (2) is not performed.

[0121] The remaining preparation parameters are the same as those in Example 1.

[0122] Comparative Example 3

[0123] The difference between this comparative example and Example 1 is that in this comparative example, the molecular sieve catalyst is 2.0 wt% Fe-UZM-35, step (1) is not performed in the preparation process, and step (2) is directly performed, and the Cu-UZM-35 in step (2) is replaced by NH4-UZM-35, and the mass ratio of NH4-UZM-35 to water is 1:1.5, and 0.045 g of ferrous chloride is used to prepare the ferrous chloride solution.

[0124] The remaining preparation parameters are the same as those in Example 1.

[0125] Comparative Example 4

[0126] The difference between this comparative example and Example 1 is that in this comparative example, the molecular sieve catalyst is 2.0 wt% Cu-UZM-35, and during the preparation process, only step (1) is performed, 5.856 g of copper acetate is added, and step (2) is not performed.

[0127] The remaining preparation parameters are the same as those in Example 1.

[0128] Comparative Example 5

[0129] The difference between this comparative example and Example 1 is that in this comparative example, the molecular sieve catalyst is 2.6wt% Cu / 0.8wt% Fe-UZM-9, and NH4-UZM-35 is replaced by NH4-UZM-9 in step (1).

[0130] The remaining preparation parameters are the same as those in Example 1.

[0131] Performance Testing

[0132] The molecular sieve catalyst samples prepared in Examples 1-15 and Comparative Examples 1-5 were tableted and sieved, and the 40-60 mesh catalyst was taken for experiment and treatment. The obtained 40-60 mesh catalyst was placed in a quartz tube, placed in a fixed bed reactor, and hydrothermally aged at 750°C for 16 hours in a 10% H2O / N2 atmosphere to explore the hydrothermal stability of the catalyst.

[0133] The molecular sieves before and after aging were placed in a chamber with [NO] = [NH3] = 500 ppm, [O2] = [H2O] = 5 vol%, N2 as the balance gas, a total flow rate of 500 mL / min, and a space velocity of 100000 h -1 The catalytic reaction test was carried out under the conditions of

[0134] The test results are shown in Table 1. Figure 1 , Figure 2 and Figure 3 As shown. Among them, T50 and T90 in Table 1 refer to NO x The temperatures required for conversions of 50% and 90%.

[0135] Table 1

[0136]

[0137]

[0138] From the data comparison of Examples 1-7 and Comparative Examples 1-5 in Table 1 and Figures 1 to 3 It can be seen that in the present invention, bimetallic Cu and Fe are loaded on the UZM-35 molecular sieve. Compared with the catalyst obtained by loading only Cu or Fe, thanks to the synergistic effect between Cu and Fe and the UZM-35 carrier, the catalyst can take into account both high and low temperature activity, and the amount of NO2 generated is low, the hydrothermal stability is good, and the active temperature window of the molecular sieve is effectively broadened; and compared with the use of other types of carriers, the use of UZM-35 molecular sieve as a carrier in the present invention is also conducive to improving the activity of the catalyst.

[0139] From the data comparison between Example 1 and Examples 8-11 in Table 1, it can be seen that changing the loading amount of Cu or Fe will affect the catalytic effect of the catalyst. In practical applications, different loading amounts of Cu and / or Fe can be selected according to the high and low temperature performance requirements of the catalyst. By controlling the loading amount of Cu and / or Fe within the range of 0.5 to 5 wt%, it is more conducive to achieving a balance between the catalytic activity at high and low temperatures.

[0140] From the data comparison between Example 1 and Examples 12-15 in Table 1, it can be seen that in the present invention, the temperature and / or time in the first, second and third calcination processes will also affect the catalytic activity of the catalyst. In practical applications, different temperatures and / or times in the first, second and third calcination processes can be selected according to the requirements for catalyst quality. By controlling the temperature at 500-800° C. and the time at 5-10 h, the stability of Cu and / or Fe loaded in the carrier can be further improved, which is more conducive to improving the activity and stability of the catalyst.

[0141] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A molecular sieve catalyst, characterized in that: The molecular sieve catalyst includes UZM-35 and Cu and Fe supported on the UZM-35.

2. The molecular sieve catalyst according to claim 1, characterized in that The Cu loading is 0.5-5wt%; Preferably, the Fe loading is 0.5-5wt%.

3. A method for preparing a molecular sieve catalyst as claimed in claim 1 or 2, characterized in that: The preparation method comprises: performing an ion exchange reaction on an NH4-UZM-35 molecular sieve and a copper source, obtaining Cu-UZM-35 after a first calcination, and then loading Fe on the Cu-UZM-35 in an iron source solution, and obtaining Cu / Fe-UZM-35 after a second calcination and a third calcination.

4. The method for preparing a molecular sieve catalyst according to claim 3, characterized in that: The copper source includes any one of copper nitrate, copper acetate or copper carbonate, or a combination of at least two thereof; Preferably, the ion exchange reaction comprises: dispersing NH4-UZM-35 molecular sieve in a solvent, adding a copper source, and performing ion exchange; Preferably, the solid-liquid ratio of the NH4-UZM-35 to the solvent is 1:(20-150); Preferably, the temperature of the ion exchange reaction is 40 to 100°C; Preferably, the ion exchange reaction time is 5 to 24 hours; Preferably, the ion exchange reaction is carried out under stirring, and the stirring speed is 100-1000 r / min.

5. The method for preparing a molecular sieve catalyst according to claim 3 or 4, characterized in that: The product after the ion exchange reaction is subjected to a first cooling process, a first solid-liquid separation process, a first washing process and a first drying process in sequence; Preferably, the first drying temperature is 80-180°C; Preferably, the first drying time is 8 to 24 hours; Preferably, the heating rate of the first calcination is 0.5-10°C / min; Preferably, the temperature of the first calcination is 500-800°C; Preferably, the first calcination holding time is 5 to 10 hours.

6. The method for preparing a molecular sieve catalyst according to any one of claims 3 to 5, characterized in that: The Fe loading method includes any one of the incipient wetness impregnation method, the impregnation method or the ion exchange method, preferably the incipient wetness impregnation method; Preferably, the iron source includes any one of ferrous chloride, ferrous acetate, ferrous sulfate or ferrous oxalate, or a combination of at least two thereof.

7. The method for preparing a molecular sieve catalyst according to claim 6, characterized in that: The incipient wetness impregnation method comprises: adding the iron source solution dropwise into the Cu-UZM-35 under grinding conditions and allowing to stand; Preferably, the mass ratio of the Cu-UZM-35 to the solvent in the iron source solution is 1:(1-5); Preferably, the grinding temperature is 20 to 60°C; Preferably, the grinding time is 0.5 to 3 hours; Preferably, the standing time is 1 to 24 hours; Preferably, the second calcination is carried out in a protective gas atmosphere, preferably nitrogen; Preferably, the heating rate of the second calcination is 0.5-10°C / min; Preferably, the temperature of the second calcination is 500-800°C; Preferably, the second calcination holding time is 5 to 10 hours.

8. The method for preparing a molecular sieve catalyst according to any one of claims 3 to 7, characterized in that: sequentially performing a second solid-liquid separation, a second washing, and a second drying treatment on the product after the second calcination; Preferably, the second drying temperature is 80-180°C; Preferably, the second drying time is 8 to 24 hours; Preferably, the third calcination is carried out in an air atmosphere; Preferably, the heating rate of the third calcination is 0.5-10°C / min; Preferably, the temperature of the third calcination is 500-800°C; Preferably, the insulation time of the third calcination is 5 to 10 hours.

9. The method for preparing a molecular sieve catalyst according to claim 3, characterized in that: The preparation method comprises the following steps: (1) NH4-UZM-35 and a solvent are mixed at a solid-liquid ratio of 1:(20-150), a copper source is added thereto, and then an ion exchange reaction is carried out at 40-100° C. for 5-24 hours at a stirring speed of 100-1000 r / min, and after cooling, solid-liquid separation and washing, a first drying treatment is carried out at 80-180° C. for 8-24 hours, and the temperature is increased to 500-800° C. at a heating rate of 0.5-10° C. / min, and the temperature is kept for 5-10 hours to obtain Cu-UZM-35; (2) according to the mass ratio of Cu-UZM-35 to solvent being 1:(1-5), a solvent is added to an iron source to prepare an iron source solution, and then the iron source solution is added dropwise to the Cu-UZM-35 under grinding conditions of 20-60°C. After the process lasts for 0.5-3h, the mixture is allowed to stand for 1-24h. Subsequently, the mixture is heated to 500-800°C at a heating rate of 0.5-10°C / min in a nitrogen atmosphere, and kept warm for 5-10h. The product after the first calcination is filtered and washed in turn, and then dried at 80-180°C for 8-24h. Then, the mixture is heated to 500-800°C at a heating rate of 0.5-10°C / min in an air atmosphere, and kept warm for 5-10h to obtain Cu / Fe-UZM-35. The copper source includes any one of copper nitrate, copper acetate or copper carbonate, or a combination of at least two thereof; The iron source includes any one of ferrous chloride, ferrous acetate, ferrous sulfate or ferrous oxalate, or a combination of at least two thereof.

10. Use of the molecular sieve catalyst according to claim 1 or 2 in the conversion of nitrogen oxides.